Psychophysiological whole‐brain network clustering based on connectivity dynamics analysis in naturalistic conditions. Issue 12 (1st August 2016) - Raz, Gal; Shpigelman, Lavi; Jacob, Yael; Gonen, Tal; Benjamini, Yoav; Hendler, Talma
Abstract: We introduce a novel method for delineating context‐dependent functional brain networks whose connectivity dynamics are synchronized with the occurrence of a specific psychophysiological process of interest. In this method of context‐related network dynamics analysis (CRNDA), a continuous psychophysiological index serves as a reference for clustering the whole‐brain into functional networks. We applied CRNDA to fMRI data recorded during the viewing of a sadness‐inducing film clip. The method reliably demarcated networks in which temporal patterns of connectivity related to the time series of reported emotional intensity. Our work successfully replicated the link between network connectivity and emotion rating in an independent sample group for seven of the networks. The demarcated networks have clear common functional denominators. Three of these networks overlap with distinct empathy‐related networks, previously identified in distinct sets of studies. The other networks are related to sensorimotor processing, language, attention, and working memory. The results indicate that CRNDA, a data‐driven method for network clustering that is sensitive to transient connectivity patterns, can productively and reliably demarcate networks that follow psychologically meaningful processes. Hum Brain Mapp 37:4654–4672, 2016 . ©2016 Wiley Periodicals, Inc.